Analysis on Combustion Process of a 396 Series Diesel Engine with Flat-top Convex Basin Combustion Chamber. Issue 4 (March 2020) - Liang, Yu; Zhou, Liying; Xu, Mingfei; Yao, Guwen
Abstract: The 396 series diesel engine has been widely used in many fields in China. The combustion process of the 396 series diesel engine with flat-top convex basin combustion chamber is analyzed by using the computational fluid dynamics software FIRE, and a 3D combustion model was established. The fuel spray, ignition start point, combustion pressure, combustion heat release rate, average temperature in cylinder and NO emission were compared and analyzed when the 5-hole, 6-hole and 8-hole uniformly distributed injectors were adopted. When injectors with different injection holes are adopted, the ignition delay period is basically the same and the fire occurs in the same place. The proper number of injector hole shall be selected to enlarge the space area occupied by fuel spray. The 6-hole injector is featured by higher pressure in the combustion cylinder, higher average temperature, better combustion process, higher thermal efficiency and higher NO emission. This research result provides a basis for selecting suitable injector for the 396 series diesel engine with flat-top convex basin combustion chamber.